Interpreting vegetation change in tropical arid ecosystems from sediment molecular fossils and their stable isotope compositions: A baseline study from the Pilbara region of northwest Australia - Rouillard, A.; Greenwood, P.; Grice, Kliti; Skrzypek, G.; Dogramaci, S.; Turney, C.; Grierson, P. (Elsevier BV, 2016)
Detection of source diagnostic molecular fossils (biomarkers) within sediments can provide valuable insights into the vegetation and climates of past environments. However, hot and arid regions offer particularly challenging interpretive frameworks for reconstructions because baseline data are scarce, organic matter is generally very low and in the inland tropics in particular, sediments are also often subject to flooding and drought. Here, we investigated whether biomarkers and compound-specific δ13C values could be extracted from a late Holocene sediment record from the Fortescue Marsh (Pilbara, northwest Australia) to allow interpretation of past catchment vegetation and hydroclimate. The low total carbon (TC) content (< 1.4%) was a major challenge for the molecular analyses over the ~ 2000 years old sequence. Nevertheless, they revealed that the dominant hydrocarbon features (e.g., long chain n-alkanes) indicative of terrestrial plants (e.g., C4 grasses; riparian and other C3 plants) encompassed the last ~ 1300 yrs and that low abundance of products from aquatic sources (e.g., n-C17) were detected in the uppermost sediments only when permanently inundated conditions prevailed (recent decades). Similarly, the lower δ13C values (i.e., a difference of − 2.3‰) of long chain n-alkanes in upper sediments reflected a vegetation response to the emergence of wetter conditions through the late Holocene in the region.Based on the diverging dominant source contributions obtained from the molecular distributions and arid based Bayesian mixing model (δ13C of n-C27–33 alkanes) results, less arid conditions may have favoured the input of 13C depleted n-alkanes from the Eucalyptus (C3) dominant riparian vegetation. The deepest sediments (< 700 CE) however, had a TC content of < 0.4%, and no organic compounds were detected, consistent with local and regional records of hyperarid conditions. These results demonstrate that n-alkanes can provide a molecular and stable isotopic fingerprint of important - and perhaps underappreciated - ecological processes in modern tropical arid environments for future paleoclimate investigations.